Improving of Degraded Soil Quality for Ficus variegata Nursery Media by Adding Organic Matters and NPK Fertilizer - Danu Danu; Dede Jajat Sudrajat (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2019)
The availability of topsoil which is relatively fertile to use as seedling media is more and more limited so that the low nutrient degraded soil become alternative media for tree seedling nursery. The purpose of the research was to get the combination of degraded soil media mixture for nyawai (Ficus variegata) seedling media in nursery. The degraded soil collected in the heavy eroded soil in Rumpin Villages, Rumpin Sub District, Bogor. Completed random design with factorial was used to test the media mixture treatments and NPK fertilizer dosages on the growth of nyawai seedling. A pair of leaves seedlings was transplanted on 5 media treatments, i.e. top soil, degraded soil, degraded soil 70 % + compost 30 % (v:v), degraded soil 90 % + rice husk charcoal 10 % (v:v), and degraded soil 60 % + compost 30 % + rice husk charcoal 10 % (v/v). The dosage of NPK fertilizer was used as much: 0 g, 0.5 g polybag, and 1.0 g/polybag. The result showed that interaction of media and NPK fertilizer dosages was only affected on seedling biomass parameter. The interaction treatment of the mixture media of degraded soil 60 %, compost 30 % and rice husk charcoal 10 % could increase the growth of nyawai seedlings high by 30.60 % and fertilizer treatment of 1 g NPK could increase seedling biomass 6.21 g. The mixture media and fertilizing treatment by NPK 1 g can be alternative media on nyawai nursery.Keywords: Ficus variegata, soil media, seedlings, growth